PENGETAHUAN (TEKNOLOGI, PEDAGOGIK DAN KONTEN) PEMBELAJARAN DITINJAU DARI FAKTOR GAMESECAF GURU - Alfian Erwinsyah; Putriani L. Maliki; Erni Mohamad; Masitha Cania Midu (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to produce a valid and reliable instrument of Knowledge (technology, pedagogic and content), to analyze the relationship between variable values of Knowledge (technology, pedagogic and content) of teachers in learning, to analyze Knowledge (technology, pedagogic and content) of teachers in learning based on GAMESECAF factors. This research uses Survey research with Cross Sectional Survey technique. This research was conducted at 7 Madrasah Aliyah in Gorontalo city. A population of 185 teachers was taken as a sample of 127 respondents. Data collection techniques in the form of questionnaires and the results of the questionnaire analyzed the validity and reliability of the instrument using the Rasch Model. Analysis of the relationship between variables is described from the results of the SPSS formulation. The results of the study are (1) All questionnaire items meet the valid and reliable requirements. (2) The correlation between TPACK dimensions is in the moderately strong (5 correlations) and strong (16 correlations) categories. (3) The average percentage values are all above 80%, which proves that the respondent teachers of Madrasah Aliyah in Gorontalo city have TPACK skills in the good and very good categories